Kejadian Ketuban Pecah Dini terhadap Infeksi Neonatorum di Ruang Perinatologi RSUD Kota Madiun - Nuraisya, Wahyu; Peni Wulandari (JURNAL KEBIDANAN, 2024)
Premature Rupture of Membranes (PRM) the rupture of the amniotic membrane before delivery can have consequences for the mother and baby, and can result in neonatal infections. The aim of the study was to determine the relationship between the incidence of premature rupture of membranes and the incidence of neonatal infections in Perinatology at the Madiun City General Hospital. Type of research is correlation analytic, retrospective cohort research design with a documentation study approach. The population was all newborn babies whose mothers experienced PROM from July 2022 to July 2023. The sample was 158 mothers who gave birth using simple random sampling. Research in the Perinatology Room at Madiun City Regional Hospital starting in August 2023. Independent variable is premature rupture of membranes. Neonatal infection research variables. Analysis tests using the Chi Square Test. The results of the research that almost all respondents had a duration of KPD ≥ 12 hours, 146 people (92.4%), almost all respondents experienced neonatal infections, 124 people (78.5%), the Chi Square test produced Sig. (2-tailed) is 0.013, meaning there is a relationship between the incidence of premature rupture of membranes and the incidence of neonatal infection in the Madiun City Regional Hospital with a very weak relationship level because the relationship value is 0.195. Mothers who gave birth to KPD ≥ 12 hours did not cause neonatal infections, namely that health workers increased their self-protection to prevent infection in newborns by not frequently carrying out internal examinations on women who gave birth who experienced KPD, giving antibiotics and you need to wash your hands properly